Evaluation of drug-druginteractions in cattleusing intestinal explants - Lifschitz, Adrian Luis (2017)
The concurrent administration of drugs is currently used in veterinary medicine. In cattle, the coadministration of anthelmintics may be a useful pharmacological tool to delay the parasite resistance. Different transporter proteins such as P-glycoprotein (P-gp) are involved in the excretion process of anthelmintics.